Exploring psychological determinants of sharing donor recognition on social networking sites. Issue 3 (6th November 2019) - Chell, Kathleen; Russell‐Bennett, Rebekah; Mortimer, Gary
Abstract : Not‐for‐profit organizations (NFPs) are increasingly turning to online platforms to engage with donors. However, sharing rates of donation activity to social networking sites (SNSs) are low. Existing research has predominantly taken an aggregated approach to understanding SNS sharing behavior, therefore this study took a context‐specific approach and explored; why do donors choose to share (or not share) donor recognition on social networking sites? A qualitative research design was employed using interviews with 20 Australian donors. Social, organizational and individual factors were identified as influential to donors' decisions to share online donor recognition. This study extends understanding around online self‐disclosure and firm‐generated electronic word‐of‐mouth and provides strategic direction for NFPs to encourage greater donation sharing behavior on SNSs.